Effect Of Corporate Governance Mechanisms On The Corporate Social Responsibility Disclosure Among Saudi Listed Firms: The Mediating Role Of Level Of Corporate Governance Compliance - D Alshehri, Abdulaziz Mohammed (2022)
In 2017, the Saudi government released a new corporate governance (CG) regulation that mandated all listed firms to disclose their CSR activities in their annual report based on the requirement of the new index. Even though the Saudi listed firms are making efforts to comply with the new regulations, accurate statistics on the compliance level is still unclear. Similarly, previous research mostly focuses on the old Saudi regulations and hardly accessed the influence of the board characteristics on both the level of CG compliance and CSRD quantity and quality together. The study aimed at filling the gap by investigating the factors that determined the level of CG compliance and CSRD quantity and quality in Saudi Arabia. The data was collected using content analysis based on the annual reports of 123 Saudi nonfinancial listed companies. Due to the quantitative nature of the research, both SPSS and smart PLS-SEM software were used in analyzing the data. The CSRD quantity items were measured using five-dimension of environment, workplace, community, marketplace, and others. In contrast, for CSRD quality, eight index questions on relevance, faithful representation, understandability, and comparability were used. The findings based on the hypothesized relationships found board size and frequent board meetings to have a significant positive relationship with the level of CG compliance and CSRD quantity and quality. Similarly, the proportion of independent directors was found to have a significant negative association with the level of CG compliance and CSRD quantity and quality. However, the relationship between the proportion of the board’s ownership, the number of board’s committees, and the level of CG compliance was insignificant. On the other hand, the level of CG compliance also has a significant positive relationship with CSRD quantity and quality. The mediating relationship shows that the level of CG compliance mediates the relationship between board size, the proportion of independent directors, frequent board meeting, and CSRD quantity and quality. However, the proportion of the board’s ownership and the number of board’s committees were found to have no indirect effect on CSRD quantity and quality. The results further indicate that government ownership strengthens the relationship between the level of CG compliance and CSRD quantity and quality. Theoretically, the study contributed significantly through the introduction of government ownership and level of CG compliance as moderating and mediating variables respectively. It is concluded that the new CG regulations improve the compliance level of listed firms. The study contributes to the literature by integrating agency theory with signaling and stakeholder theory and tested the moderating effect of government ownership.